Jatropha Curcas Extract Improves Carbon Tetrachlorideinduced Nephrotoxicity And Inflammation In Rats - FAROUK K. EL-BAZ; HANAN F. ALY; SAFAA A. SAAD (International Journal of Pharma and Bio Sciences, 2015)
The aim of this research is to throw light on the therapeutic properties of Jatropha curcas leaves methanolic extract in CCl4-intoxicated female rats as compared to silymarin drug. Female rats were injected with CCl4 (0.5 ml/kg body weight) suspended in olive oil (1:9 v/v) twice a week for six consecutive weeks induced hepatic toxicity. J. curcas methanolic extract and silymarin drug were orally administrated at doses of 250 and 50 mg/kg body weight, daily for one month. Creatinine, urea, inflammatory biomarkers; C-reactive protein (C-RP), tumor necrosis factor alpha (TNF-α) and interlukin-10 (IL-10) levels were measured in rats blood serum. Moreover, histopathological investigation of kidney was performed. The present results reveal that creatinine, urea, C-RP and TNF-α levels were significantly increased in CCl4-intoxicated rats with percentages 49.54, 76.83, 90.59 and 62.73%, respectively. However, IL-10 level showed a significant decrease with percentage 49.05%. However, the current results declare that administration of intoxicated rats with 250 mg/kg b.wt. methanolic extract of J. curcas showed amelioration in the levels of creatinine, urea, C-RP, TNF-α and IL-10 with percentages of improvement reached to and 56.36, 73.99, 78.39, 54.34 and 39.43%, respectively which were documented with the ameliorative effect of J. curcas extract on renal architectures. Thus, the present results clearly indicated that, oral administration of J. curcas extract might provide an alternative approach for ameliorating nephrotoxicity associated with CCl4 toxicity.